2017
DOI: 10.1590/1807-1929/agriambi.v21n4p279-284
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of baru (Dipteryx alata Vogel) fruit

Abstract: A B S T R A C TWith the knowledge on the hygroscopic equilibrium of the baru (Dipteryx alata Vogel) fruit, the product can be adequately handled to maintain the moisture content at the levels recommended for safe storage. Thus, this paper aimed to determine the water desorption isotherms of baru fruits at temperatures of 20, 25, 30 and 35 °C, and water activity between 0.14 and 0.80, and obtain the values of isosteric heat of desorption as a function of the equilibrium moisture content of the product. The equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…The WBC of fruits is mainly determined by sugar content and surface characteristics, with convective drying resulting in minor porosity and hygroscopicity compared to other drying methods . Compared to other fruits and their by‐products, powders from berry pomace adsorb less moisture at 20/25 °C as a result of processing and compositional properties . Regarding the presumptive applications of dried berry pomace as a food ingredient, a wide range of food systems is possible, particularly sweet or savoury baked products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WBC of fruits is mainly determined by sugar content and surface characteristics, with convective drying resulting in minor porosity and hygroscopicity compared to other drying methods . Compared to other fruits and their by‐products, powders from berry pomace adsorb less moisture at 20/25 °C as a result of processing and compositional properties . Regarding the presumptive applications of dried berry pomace as a food ingredient, a wide range of food systems is possible, particularly sweet or savoury baked products.…”
Section: Resultsmentioning
confidence: 99%
“…63 Compared to other fruits and their by-products, powders from berry pomace adsorb less moisture at 20/25 ∘ C as a result of processing and compositional properties. 62,64,65 Regarding the presumptive applications of dried berry pomace as a food ingredient, a wide range of food systems is possible, particularly sweet or savoury baked products. Depending on berry variety and substitution level, the powders will have an impact on colour, rheological properties, texture and nutritional value.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…Seeds with higher moisture contents are less resistant to compression; compression increases proportionally with the decrease in moisture content and the increase in deformation (Oliveira et al, 2017). According to Gupta & Das (2000), this tendency may be owing to a gradual change in the cell matrix integrity with the reduction in moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in moisture content resulted in a linear increase in the force necessary to achieve the "bioyield point" of the range 78.78-53.10 N. This point represents the beginning of the seed's rupture. Oliveira et al (2017) reported that such a behavior may be related to a higher cellular density that occurred with water leakage during drying, i.e., number of cells per unit volume increased, thus resulting in a greater resistance to compression at lower moisture contents. Our results were in agreement with those obtained for other agricultural products, including Cuminum cyminum Linn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation